GESTÃO DE CUSTOS-CUSTEIO ABC: A IMPORTÂNCIA PARA A GESTÃO DE CUSTOS - ANA LUÍZA SILVA OLIVEIRA (2023)
The article seeks to understand the application of Activity-Based Costing (ABC), carried out in a market. The study aimed to analyze the real consumption of resources directed to purchasing and selling procedures by the main market blocks.